Foreign trade, economic growth, and causality evidence from time-series analysis for selected ASEAN countries - Aḥmad, Yūsuf; Wadhawan, Satish (Ann Arbor, MI ProQuest Dissertations & Theses Global, 1998)
"The primary concern of this study is to examine the relationship between economic growth (GDP) and the key trade variables, namely, exports and imports for five selected ASEAN countries (Thailand, Indonesia, Singapore, Malaysia, and the Philippines). The exercise uses a simultaneous equation model based on Feder's theoretical framework to examine the jointly determined relationship between GDP, exports, and imports using time-series data for the period 1960-1996. Analysis is performed at three levels. First, Augmented Dickey Fuller (ADF) test is used to detect the non-stationary behavior of the time-series data. The long-run relationship of the GDP, exports, and imports is examined using the Johansen co-integration test Second, the simultaneous equation models are estimated by using two-stage least squares procedure. Lastly, Granger causality tests are performed to analyze the nature of the feedback relationship between the various pairs of variables. The results of the ADF test suggest that all the variables, at their level, have unit roots and therefore are non-stationary. However, it is found that they become stationary in their first difference level. Johansen co-integration test suggests that even though these variables are non-stationary in their level, they are co-integrated. Their estimation can therefore still give highly consistent results. Findings of the study support the hypothesis that exports contributed to the GDP growth of these five ASEAN countries-a result which is consistent with that of other studies. However, except for Indonesia, imports have had a positive impact on the growth of the GDP of these countries. The results of the Granger causality test provide mixed signals relative to those of the previous studies. However, for all countries of the sample, export growth does cause increase in the GDP growth. The results support the view that trade liberalization, by way of relieving import constraints and/or export-led growth can contribute to the GDP growth of a country; and that exports and imports should not be considered as alternative policy options and should be adopted simultaneously."--Abstract.
Thesis (PhD)--Howard University, 1998.
Includes bibliographical references (pages 109-117) and abstract.
Keywords: International trade -- Econometric models; Economic development -- Econometric models; Time-series analysis; Electronic book; ASEAN countries -- Commerce -- Econometric models